Redeeming Time : Protestantism and Chicago's Eight-Hour Movement, 1866-1912 - Mirola, William A. (William Andrew) (Book collections on Project MUSE., 2015)
"Exploring the intersection between Chicago's eight-hour movement and Protestant religious culture over a fifty-year span, this project considers how workers and clergy contested the religious meaning of the eight-hour system and the legitimacy of legislating limitations on overwork. Showing that behind every religious appeal was a contest over whose religious meanings would define industrial conditions and conflicts in Chicago, William Mirola examines how both workers and Protestant clergy wove and rewove working-class religious cultures and ideologies into strategic and rhetorical frames around the issue of an eight-hour workday. Mirola traces the successive framing of eight-hour reform from pre-1880s, when most Protestant clergy supported long hours to keep workers from idleness, intemperance, and secular leisure activities, through the 1890s, when eight-hour support among Protestant clergy gained ground as the result of a new social consciousness spurred by intensified worker protest and ongoing employer resistance to limiting working hours, into the early decades of the twentieth century, as religious framing of the eight-hour movement declined in favor of political and economic arguments. Mirola argues that the ongoing conflicts between Chicago workers and employers transformed both how clergy spoke about the eight-hour movement and what they were willing to do, through alliances with the labor movement, to see the eight-hour day enacted as industrial policy. By examining religious framing within the eight-hour movement, the author illustrates the potential and the limitations of religious culture and religious leaders as forces in industrial reform"--